2004
DOI: 10.1002/ijc.20103
|View full text |Cite
|
Sign up to set email alerts
|

Ser‐249TP53 mutation in tumour and plasma DNA of hepatocellular carcinoma patients from a high incidence area in the Gambia, West Africa

Abstract: Hepatocellular carcinoma (HCC) is frequent in areas of high exposure to aflatoxin and high prevalence of HBV infection, such as western Africa and south-east China. A selective mutation in TP53 (AGG-->AGT at codon 249, Arg-->Ser) has been identified as a hotspot in HCCs from such areas, reflecting DNA damage caused by aflatoxin metabolites. Recent studies have shown that circulating free DNA can be retrieved from human plasma, and it is hypothesised that plasma DNA may serve as a source for biomarkers of tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 91 publications
(72 citation statements)
references
References 32 publications
4
66
0
2
Order By: Relevance
“…With the mechanistic understanding of the role of specific DNA-AFB1 adducts and the resulting formation of 249 ser mutations in hepatocytes (Smela et al, 2001), in conjunction with a significant majority of 249 ser TP53 mutations reported in the literature having been found in HCC (Hainaut and Hollstein, 2000), it is reasonable to deduce that the liver is the source of the 249 ser TP53 mutation that we detected. When we examined a limited number (17) of matched liver tumor/plasma pairs, we found concordance between tumor and plasma DNA findings in 88% (15) of cases (Szymanska et al, 2004). Similarly high concordance has been reported by Jackson et al (2001) among HCC cases from Qidong, China, a region with high HBV prevalence and AFB1 exposure.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…With the mechanistic understanding of the role of specific DNA-AFB1 adducts and the resulting formation of 249 ser mutations in hepatocytes (Smela et al, 2001), in conjunction with a significant majority of 249 ser TP53 mutations reported in the literature having been found in HCC (Hainaut and Hollstein, 2000), it is reasonable to deduce that the liver is the source of the 249 ser TP53 mutation that we detected. When we examined a limited number (17) of matched liver tumor/plasma pairs, we found concordance between tumor and plasma DNA findings in 88% (15) of cases (Szymanska et al, 2004). Similarly high concordance has been reported by Jackson et al (2001) among HCC cases from Qidong, China, a region with high HBV prevalence and AFB1 exposure.…”
Section: Discussionsupporting
confidence: 84%
“…In a preliminary study, we have shown that that 249 ser could be detected in plasma DNA from a proportion of HCC cases in The Gambia but not in HCC cases from Europe . We have also found that there was a concordance of 88% between the presence of 249 ser in the biopsy and in the plasma of the same HCC patient (Szymanska et al, 2004). In the present study, we have determined the presence of 249 ser in the plasma of over 600 subjects enrolled in a case-control study in The Gambia, to evaluate the individual and joint effects of plasma 249 ser and HBV markers on HCC development.…”
Section: Introductionmentioning
confidence: 78%
“…The size of the final PCR fragments were 237 bp (first PCR) and 177 bp (second PCR), respectively. TP53 mutation was analyzed by restriction fragment length polymorphism (RFLP) using a modified method described by Szymanska et al (2004 DOI:http://dx.doi.org/10.7314/APJCP.2013.14.6…”
Section: Detection Of R249s In Serummentioning
confidence: 99%
“…It occurs in more than 50% of patients with HCC from high incidence areas such as subSaharan Africa and East Asia (Hainaut and Hollstein 2000) and Ser-249 TP53 mutation, a missense mutation resulting in substitution of arginine with serine at codon 249, reflects high dietary exposure to aflatoxins (Hsu et al 1991). A few studies reported the feasibility of detection of Ser-249 mutation in cfDNA derived from plasma or serum of HCC patients (Szymańska et al 2004;Kirk et al 2005;Hosny et al 2008) highlighting the potential role of using circulating mutant DNA in diagnosis of HCC.…”
Section: Hepatocellular Carcinomamentioning
confidence: 99%